Editorial - Preudhikulpradab, Sirichai (ABAC ODI JOURNAL Vision. Action. Outcome, 2025)
This issue of 19 articles provides comprehensive, evidence-based research findings for practitioners, scholars, and policymakers working at the intersection of organizational growth and societal well-being across Asia. From corporate settings to educational institutions, the studies examine the crucial role of adaptive leadership and organizational strategies in navigating rapid change, including technological advancements, regulatory shifts, and evolving consumer behaviors. The current collection also highlights how individual psychological capacities, including self-regulation and growth mindsets, combined with experiential learning, positively influence academic achievement and personal development within teaching and learning environments, including the effects of leadership on teacher satisfaction and how blended learning bolsters students’ learning ability, and enhances student engagement and learning outcomes. In a corporate setting, studies highlight the significance of customer satisfaction, innovation, and cultural experiences in stimulating economic growth and community development. Analysis of service quality in entrepreneurial ventures, and the integration of cultural tourism, exemplify how experiential and socio-cultural factors contribute to destination branding and local economies. How leadership styles, self-efficacy, social support, and culture shape organizational outcomes, employee motivation, well-being, retention, and inclusivity are also investigated within the context of family business and SMEs. We, the ABAC ODI Journal editorial team, are pleased to welcome you to a journey of growth and discovery through the very insightful studies contributed by local and international scholars, which help us cultivate new ideas and explore innovative solutions to drive conscious, sustainable change in organizations, industries, and communities.